Police and political violence in the 1960s and 1970s Germany and Italy in a comparative perspective - Reiter, Herbert (European review of history, 2007)
Notwithstanding the significant differences between the German and Italian police models (federal and civil vs. centralised and militarised), in both countries the confrontation with the protest movements of the 1960s and 1970s had a profound impact on police conceptions and public order strategies. Police forces in some German federal states (West Berlin) followed a hard line until the late 1960s, while in others (Munich, Hamburg) reforms to the Weimar-centred police intervention tactics took place beginning in the early to mid-1960s. In Italy, traditional police conceptions and strategies remained largely unchanged and re-emerged in 1968 ...